Framing of the 1MDB financial scandal : A comparative study of the coverage by The Star and Malaysiakini - Ting, Su Hie; Murudi, Thanaraj (Taylor's SEARCH Journal of Media and Communication Research, 2019)
This paper looks at the framing of a financial scandal involving top government officials by a mainstream news medium (The Star) and an alternative news medium (Malaysiakini) before the historic change of the country’s ruling party. In particular, the paper reveals why a financial scandal became politicised, and how a controversial issue was framed within the context of lawsuit threats and newspaper permit suspension. A total of 815 straight news articles from 1 July to 30 September 2016 published in The Star (185 articles) and Malaysiakini (630 articles) were analysed. The quantitative content analysis revealed that headlines generally contained two to three dimensions, and The Star had typically longer and more multi-dimensional headlines. The political, constitution and jurisprudence dimensions dominated the 1Malaysia Development Berhad (1MDB) news headlines, accounting for 56.7% of 1,619 dimensions identified. Although 1MDB was a financial scandal, only Malaysiakini framed it as such while The Star downplayed the effect of the alleged embezzlement of 1MDB funds on the Malaysian economy. As for the crime and justice dimension, The Star focused on details of the unfolding events whereas Malaysiakini highlighted suspects of the alleged embezzlement and sacking of high-ranking government officers assisting the investigation. There is a stark contrast evident in the framing of the morality dimension of 1MDB news articles with The Star presenting the government voice, whereas Malaysiakini carried the voice of the opposition leaders and religious heads. The findings indicate that The Star was more guarded in framing 1MDB news compared to Malaysiakini.